CO76 - Observational Study Research, Audit & Feedback, Or Benchmarking (One Of Them Or All Together?) - Cruz, Maria Dulce (2016)
The potential of a research project about the epidemiology of painful procedures in neonates involving audit, feedback and benchmarking of current practices, to improve the quality of pain management.